Lipoprotein lipase - Martin Merkel; Robert H. Eckel; Ira J. Goldberg (Journal of Lipid Research, 2002)
Lipoprotein lipase (LPL) regulates the plasma levels of triglyceride and HDL. Three aspects are reviewed. 1) Clinical implications of human LPL gene variations: common mutations and their effects on plasma lipids and coronary heart disease are discussed. 2) LPL actions in the nervous system, liver, and heart: the discussion focuses on LPL and tissue lipid uptake.3) LPL gene regulation: the LPL promoter and its regulatory elements are described.